Karakteristik Kabupaten dan Kota di Indonesia dengan Masalah Gizi Ganda pada Penduduk Dewasa Tahun 2018 - Karizma Rindu Inayatullah; Kusharisupeni Djokosujono; Rizky Prayogo Ramadhan (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2022)
Economic transitions, industrialization, urbanization, and technological shifts in developing countries have led to nutrition transitions, which has impact on the incidence of double burden malnutrition. This study aims to identify districts/cities with adult double burden malnutrition (DBM) as well as to analyze the characteristics of the region. The design of this research is an ecological study. Samples are 371 districts/cities with adult nutritional problems based on Riskesdas 2018, which categorized into undernutrition, overnutrition, and DBM region. Regional characteristics are classified based on the national figures. Samples were analyzed by spatial and bivariate analysis. There were 38 districts/cities (10.2%) in Indonesia that experienced adult DBM, with the highest number on Java island. The PPH score (87.01), protein intake (63.92 grams/cap/day), proportion of population with sufficient physical activity (62.93%), percentage of poor population (7.95 %), population density (2968 people/km2) and average length of schooling (9.35%) were not significantly different between DBM and overnutrition region (p>0.05). Harvested area (26 890.58 Ha), rice production (152.899.76 Tons/GKG), and rice productivity (152.899.76 Ku/Ha) were not significantly different between DBM and undernutrition region (p>0.05). The DBM region is a districts/cities that has undergone agricultural and economic transformation, resulting in changes in food consumption patterns and physical activity of the population. The incidence of adult DBM in districts/cities is more related to regional characteristics that increase the prevalence of overnutrition. Keywords: adult double burden malnutrition, nutrition transition, ecological study